Bible Translation as Incarnation of the Word of God: Transformational Power through Form and Meaning - Winedt, Marlon (The Bible translator, 2021)
Bible translation is not a neutral activity, divested of any moral, spiritual, or cultural claim or responsibility. Form has often distorted meaning but happily meaning has often created new hybrid forms in different cultures. This paper addresses the need to work out the incarnational aspect of Bible translation in terms of a conscious multimodal perspective. First, there is a need for a philosophical-theological account of the dialectical relationship between form and meaning. Second, we need to reinterpret the relationship among different types of embodied performance, such as oral and written translation, as part of the same multimodal reality. Finally, Bible translation should promote the appropriation of Scripture through the community’s culture in different forms in order to unleash its transformational power. Multimodal theory can offer a valuable tool to treat all types and modes of translation as equal, but distinct, expressions, thus acknowledging different cultures, people groups, and communities of faith.